Correlation analysis of the impact of Clonorchis sinensis juvenile on gut microbiota and transcriptome in mice - Xueling Deng; Shitao Li; Yuhong Wu; Jiali Yao; Wei Hou; Jiangyao Zheng; Boying Liang; Xiaole Liang; Qiping Hu; Zhanshuai Wu; Zeli Tang (Microbiology Spectrum)
ABSTRACT Clonorchiasis remains a non-negligible global zoonosis, imposing serious socio-economic burdens in endemic regions. The interplay between gut microbiota and the host transcriptome is crucial for maintaining health; however, the impact of Clonorchiasis sinensis juvenile infection on these factors is still poorly understood. This study aimed to investigate their relationship and potential pathogenic mechanisms. The BALB/c mouse model of early infection with C. sinensis juvenile was constructed. Pathological analyses revealed that C. sinensis juvenile triggered liver inflammation, promoted intestinal villi growth, and augmented goblet cell numbers in the ileum. Additionally, the infection altered the diversity and structure of gut microbiota, particularly affecting beneficial bacteria that produce short-chain fatty acids, such as Lactobacillus and Muribaculaceae, and disrupted the Firmicutes/Bacteroidetes ratio. Gut transcriptome analysis demonstrated an increase in the number of differentially expressed genes (DEGs) as infection progressed. Enriched Gene Ontology items highlighted immune and detoxification-related processes, including immunoglobulin production and xenobiotic metabolic processes. Kyoto Encyclopedia of Genes and Genomes pathway analysis further indicated involvement in circadian rhythm, as well as various detoxification and metabolic-related pathways (e.g., glutathione metabolism and glycolysis/gluconeogenesis). Prominent DEGs associated with these pathways included Igkv12-41, Mcpt2, Arntl, Npas2, Cry1, and Gsta1. Correlation analysis additionally identified Bacteroides_sartorii as a potential key regulator in the interaction between gut microbiota and transcriptome. This study sheds light on the alterations in gut microbiota and transcriptome in mice following C. sinensis juvenile infection, as well as their correlation, laying a foundation for a better understanding of their interaction during infection.IMPORTANCEThis study highlighted the impact of C. sinensis juvenile infection on the gut microbiota and transcriptome of BALB/c mice. It induced liver inflammation, promoted intestinal villi growth, and altered goblet cell numbers. The infection also disrupted the diversity and structure of gut microbiota, particularly affecting beneficial bacteria. Transcriptome analysis revealed increased expression of genes related to immune response and detoxification processes. Important pathways affected included circadian rhythm, glutathione metabolism, and glycolysis/gluconeogenesis. Notable genes implicated included Igkv12-41, Mcpt2, Arntl, Npas2, Cry1, and Gsta1. Bacteroides_sartorii emerged as a potential key regulator in this interaction.